Congenital diaphragmatic hernia: Impact of contemporary management strategies on perinatal outcomes. (8th November 2018) - Lee, Han‐Shin; Dickinson, Jan E.; Tan, Jason KG; Nembhard, Wendy; Bower, Carol
Abstract: Objective: This study aims to review temporal changes in perinatal management and 1‐year survival outcomes of cases of congenital diaphragmatic hernia (CDH) from 1996 to 2015 in Western Australia (WA). Method: This research is a retrospective study of all cases of CDH in WA from 1996 to 2015 identified from five independent databases within the WA health network. Detailed information pertaining to pregnancy and survival outcomes were obtained from review of maternal and infant medical records. Results: There were 215 cases of CDH with 164 diagnosed prenatally. Between 1996 and 2010, a decline in live birth rates for CDH‐affected pregnancies was observed, reaching a nadir of 5.3 per 10 000 births before increasing to a peak of 9.73 per 10 000 births in 2011‐2015. A corresponding decline was seen in the number of pregnancies terminated in the same period from 8.3 to 4.6 per 10 000 births ( P  = 0.14) and an increase in survival of live births from 38.9% to 81.3% ( P  = 0.01). Conclusion: The improved overall survival rate in infants with CDH over the last 20 years may have resulted in an increased tendency for women to continue their pregnancy with a concomitant decline in termination rates. Information from this study will help in the counselling of women following prenatal detection of CDH. Abstract : What is known about this topic? Congenital diaphragmatic hernia (CDH) results in high neonatal morbidity and mortality related to the severity of pulmonary hypoplasia and pulmonary hypertension. Neonatal mortality increases when associated with other major fetal anomalies or when associated with known genetic syndrome or karyotype abnormality. What does this study add? Advances in postnatal management of infants with CDH have been associated with an increased tendency for continuation of pregnancy and a concomitant decline in termination rates, especially in isolated cases.